2019
DOI: 10.3390/jimaging5050052
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Meets Hyperspectral Image Analysis: A Multidisciplinary Review

Abstract: Modern hyperspectral imaging systems produce huge datasets potentially conveying a great abundance of information; such a resource, however, poses many challenges in the analysis and interpretation of these data. Deep learning approaches certainly offer a great variety of opportunities for solving classical imaging tasks and also for approaching new stimulating problems in the spatial–spectral domain. This is fundamental in the driving sector of Remote Sensing where hyperspectral technology was born and has mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
146
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(146 citation statements)
references
References 217 publications
(284 reference statements)
0
146
0
Order By: Relevance
“…In future research, we intend to integrate microwave remote sensing and higher resolution data to reduce the impact of cloud cover, snow cover, and melt ponds on sea ice detection. In addition, because of the great potential of deep learning in automatic feature extraction and learning model building, it is widely used in various fields [41]. However, it requires large datasets and long training time.…”
Section: Discussionmentioning
confidence: 99%
“…In future research, we intend to integrate microwave remote sensing and higher resolution data to reduce the impact of cloud cover, snow cover, and melt ponds on sea ice detection. In addition, because of the great potential of deep learning in automatic feature extraction and learning model building, it is widely used in various fields [41]. However, it requires large datasets and long training time.…”
Section: Discussionmentioning
confidence: 99%
“…Deep learning has recently shown remarkable results in many computer vision application [66], [67]. A recent review [68] reported several applications of deep learning for hyperspectral imagery. In the paper [69], a convolution neural network (CNN) has been proposed for the sparse band selection of hyperspectral face recognition.…”
Section: Deep Learning and Hyperspectral Imagingmentioning
confidence: 99%
“…In recent years, deep learning, a more advanced machine learning algorithm capable of learning complex relationships, extracting feature patterns and directly building predictive models from big data, has been applied in numerous fields . Many studies have reported excellent deep learning model performances in the chemistry and biology fields. In this study, we applied a self‐designed convolutional neural network framework named DeepIR to the pulmonary edema fluid spectra involving five causes of death to assess its performance in determining the cause of death.…”
Section: Introductionmentioning
confidence: 99%